The Campus Canopy, 1939-11-10 - The Campus Canopy, The Georgia State Woman's College (The Georgia State Woman's College, 1939)
The Campus Canopy, November 10, 1939. Vol. 6, No. 5. -- Something About A Soldier -- Jane Ellen Smith, Of Fitzgerald, Will Steer The Freshmen As Class President -- Joan Crawford Paged At G. S. W. C. -- 25 Appointed To Positions On Campus Canopy -- Kappas And Lambdas Will Renew Plaque Fight On November 15 -- Smart Will Make Yearly Visit To Campus -- “Hearts” To Be Given By Seniors -- Jacksonville Bound -- Hawks Will Speak At Senior Honor Society On Tuesday -- 6 Per Cent Of Freshmen Combine Beauty And Brains -- Canopy To Sponsor Find Of Oomph Girl -- De Ovies Presented By Wymodausis Club -- IRC Honors New Members At Dinner
Digitized from original print, Valdosta State University Archives and Special Collections, December 5, 2016.
Keywords: The Campus Canopy; 1930s; 1939; The Georgia State Woman's College; GSWC; Valdosta State College; VSC; Valdosta State University; VSU